Comparative Efficacy and Safety of Anterograde vs. Retrograde Iodine Staining During Esophageal Chromoendoscopy: A Single-Center, Prospective, Parallel-Group, Randomized, Controlled, Single-Blind Trial - Tian, Xu; Yang, Wei; Chen, Wei-Qing (Frontiers in Medicine, 2021)
Background and aim: Chromoendoscopy with iodine staining is an important diagnostic method for esophageal carcinomas or precancerous lesions. Unfortunately, iodine staining can be associated with numerous adverse events (AEs). We found that the start position of spraying iodine solution is likely the main reason of causing AEs. We conducted this study to determine if clinical outcomes from anterograde iodine staining were superior to those achieved after retrograde iodine staining. Methods: A total of 134 subjects with a health risk appraisal flushing (HRA-F) score of > 6 for esophageal cancer were randomly assigned to receive anterograde or retrograde iodine staining in esophagus. The primary endpoints were the pain and the amount of iodine solution consumption. The secondary endpoints were iodine-staining effect, detection yield and response to starch indicator. Results: Nine patients suffered from pain and 6 patients revealed positive response to starch indicator in retrograde iodine staining group, however no patient reported pain (0/67) and all patients revealed a negative response to starch indicator in anterograde iodine staining group. The amount of iodine solution consumption in anterograde iodine staining group (4.97 mL) was significantly lower than that (6.23 mL) in retrograde iodine staining group, however the iodine-staining effect and detection yield were comparable between two groups. Conclusions: Antegrade iodine staining during Lugol chromoendoscopy appears to be as effective, but significantly safer than retrograde iodine staining.